Plantparasitic nematodes associated with root and tuber crops in Uganda - Coyne, Danny L.; Talwana, Herbert A.L.; Maslen, N.R. (2003)
In a nematode survey of eight commonly grown root and tuber crops (cassava, sweet potato, potato, yam, tannia, taro, carrot and turmeric) from 430 fields in Uganda, 69 species of plant-parasitic nematodes representing 28 genera were extracted from soil and roots. About twice as many nematode species were recovered from soil (64) as from roots (36), while 32 species were found only in soil and four species only in roots, usually in mixed populations. Meloidogyne spp. (root-knot nematodes) were the most frequently recovered across crops, with the major species (M. arenaria, M. hapla, M. incognita and M. javanica) observed on cassava. Some nematodes were recovered only from specific crops. Sweet potato yielded the greatest diversity of species (55 species in 25 genera), followed by cassava (40 species in 19 genera) and yam, which was sampled principally in the northern and eastern regions of Uganda (39 species in 14 genera). Results of the study provide baseline information for more detailed local population studies and nematode pathogenicity evaluations on important root and tuber crops